Moving towards effective therapeutic strategies for Neuronal Ceroid Lipofuscinosis - Geraets, Ryan D. (Orphanet J Rare Dis, 2016)
The Neuronal Ceroid Lipofuscinoses (NCLs) are a family of autosomal recessive neurodegenerative disorders that annually affect 1:100,000 live births worldwide. This family of diseases results from mutations in one of 14 different genes that share common clinical and pathological etiologies. Clinically, the diseases are subcategorized into infantile, late-infantile, juvenile and adult forms based on their age of onset. Though the disease phenotypes may vary in their age and order of presentation, all typically include progressive visual deterioration and blindness, cognitive impairment, motor deficits and seizures. Pathological hallmarks of NCLs include the accumulation of storage material or ceroid in the lysosome, progressive neuronal degeneration and massive glial activation. Advances have been made in genetic diagnosis and counseling for families. However, comprehensive treatment programs that delay or halt disease progression have been elusive. Current disease management is primarily targeted at controlling the symptoms rather than “curing” the disease. Recognizing the growing need for transparency and synergistic efforts to move the field forward, this review will provide an overview of the therapeutic approaches currently being pursued in preclinical and clinical trials to treat different forms of NCL as well as provide insight to novel therapeutic approaches in development for the NCLs.